Dwa osiemnastowieczne inwentarze zamku w Raciążku koło Ciechocinka - Kajzer, Leszek (Acta Universitatis Lodziensis. Folia Archaeologica, 1984)
This article is a publication of two 18th century inventories from Raciążek Castle in Kujawy, Włocławek Province. Thie castle is being examined by the Department of Archaeology, University of Łódź since 1978. Besides field studies there is also conducted search in the archives which unearthed two inventories not published so far. The castle of Włocławek bishops at Raciążek was undergoing numerous changes over the past centuries. When in 1330 a timber-earth castrum was destroyed, a brick Gothic castle was erected in its place to be next remodelled into a late-Renaissance residence by bishop Hieronim Rozdrażewski in the late 16th century. The next remodelling was initiated by Krzysztof Szembek (1720-1738) and completed by Walenty Czapski (1751). It was then that a considerable part of old walls was pulled down shaping the main castle buildings into a late-baroque palace. Both inventories were found in Diocesan Registry at Włocławek in books of property inventories acts. The first one (1720) contained in book No.148 registers the state of a deserted castle when all housing and residential functions were performed by a wooden "palace" erected at the beginning of 18th century on the approaches to the castle. The other inventory (from 1751) contained in book No. 156, depicts the state of the residence after remodellings of K. Szembek and W. Czapski containing an excat description of "Italian" palace and auxuliary buildings. The descriptions published in this article were utilised only by W. Górzyński, the author of the first monograph devoted to the history of the castle (1913). Both inventotires are a valuable source allowing a better insight into the history of the castle at Raciążek in the late stages of its development.